The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1093/neuonc/noy135
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific gene and pathway modeling of inherited glioma risk

Abstract: These results provide additional evidence that there may be differences by sex in genetic risk for glioma. Additional analyses may further elucidate the biological processes through which this risk is conferred.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 52 publications
(70 reference statements)
1
21
0
Order By: Relevance
“…The criteria for selecting variables conformed to clinical relevance and multivariate Cox analysis [37]. It has been reported that age, IDH status and sex are associated with the incidence rate or prognosis of glioma [1, 3840]. Considering the clinical factors of glioma, these parameters (ARL3 expression level, age, sex, WHO grade and IDH status) were included in the predictive model.…”
Section: Resultsmentioning
confidence: 99%
“…The criteria for selecting variables conformed to clinical relevance and multivariate Cox analysis [37]. It has been reported that age, IDH status and sex are associated with the incidence rate or prognosis of glioma [1, 3840]. Considering the clinical factors of glioma, these parameters (ARL3 expression level, age, sex, WHO grade and IDH status) were included in the predictive model.…”
Section: Resultsmentioning
confidence: 99%
“…We used PASCAL to compute pathway-scored ( 36 38 ). In this approach, genetic markers SNPs were first mapped to genes, and the association scores of all genes in the pathway were computed.…”
Section: Methodsmentioning
confidence: 99%
“…However, pinpointing the causative variation is more di cult. To reveal the mechanism through which a mutation site affects a phenotype and to perform subsequent functional research, GWAS joint analysis on multiple genomic levels can be used and biological pathway analysis can be applied to detect the superposition of multiple minor genes by examining genes involved in the same biological pathway, thus enabling deeper mining of GWAS data [10][11][12][13]. With the development of genome sequencing technology and the continuous improvement of statistical methods, GWAS is expected to be more e ciently applied to gene identi cation for important traits in livestock and poultry and to play an increasingly important role in animal breeding.…”
Section: Introductionmentioning
confidence: 99%